The Nigerian policy on critical information infrastructure - Saulawa, Mu'azu Abdullahi; Abdul Ghani Azmi, Ida Madieha; Zulhuda, Sonny; Ismail, Suzy Fadhilah (Universitas Muhammadiyah Yogyakarta, 2017)
The relevance of critical information infrastructure is crucial to every nation. The National Critical Information Infrastructure (NCII) of Nigeria consists of critical national resources requiring the protection of the law, and the national security services. Any attack on the information resources of a nation would definitely damage the wider national resources as well the economy. Attacks on the NCII were commonplace and directed at information communication technology systems, which are critical infrastructures and fundamental for the operation of the wider national infrastructure. The objectives of the paper are to examine the provisions of the NCII under the Nigerian Cybercrime Act 2015, to examine the relevant attacks on the Nigerian NCII and few cyber activities relating to fraud. The problems of Nigeria in relation to cybercrimes are the implementation of the law, management of its operation and special prosecutors. The methodology adopted is doctrinal approach by examining the primary and secondary data, the statutes, case report and few responses from the interviews conducted. The findings of the paper reveal that the Nigerian Cybercrime Act 2015 has adequately addressed cybercrimes, but requires some amendments, particularly in the context of cyber warfare in relation to NCII. The paper recommends that the country should embark on public enlightenment on the danger of these attacks.